Multi-location evaluation of yield component character and proximate analysis of cowpea grown in Lampung Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wahyudi A, Syukur M. 2021. Multi-location evaluation of yield component character and proximate analysis of cowpea grown in Lampung Province, Indonesia. Biodiversitas 22: 4246-4253. Cowpea has the potential to be developed in eastern Indonesia, especially Sulawesi, West Nusa Tenggara, East Nusa Tenggara, and Maluku with an altitude of less than 1000 m above sea level. Cowpea is also able to adapt to acid soils, making it possible to be developed in the dry acid soils of Sumatra and Kalimantan. To identify genotypes of high-yielding cowpea suitable for lowland areas, it is necessary to evaluate the multi-location of superior cowpea genotypes in different agroecology in the region. Multi-site evaluation trials of plant cultivars are of great importance given the obvious inconsistencies in genotype performance across different environments. This study used materials consisting of 4 varieties produced by the IPB University (Albina, Tampi, Uno, Arghavan) and 3 varieties from Balitkabi (KT-1, KT-7, and KT-9). This research is part of the preparation for the release of cowpea new varieties. The statistical analysis of the new varieties (Albina, Tampi, Uno, and Arghavan) compared with control (KT-1, KT-7, and KT-9) showed significant differences in seed productivity, carbohydrate content in old seeds, flowering, harvesting age in young pods and dry seeds. This result indicated that Albina, Tampi, Uno, and Arghavan varieties were potential for the release of new cowpea varieties, especially in the lowland areas.
Keywords: Characterization, cowpea, evaluation, multilocation, variety